Epidemiological, clinicopathological, and economic aspects of an outbreak of botulism in beef cattle in the State of Tocantins, Brazil - Helayel, Michel Abdalla; Lopes, Samara de Paula; Ramos, Adriano Tony; Cunha, Isabelle Magalhães da; Ramos, Luiz Filipe Cabral de Souza; Dutra, Iveraldo dos Santos; Carvalho, Vivian de Assunção N.; Caldas, Saulo Andrade (Brazilian Journal of Veterinary Medicine, 2019)
The objective of this work was to quantify the economic losses caused by a botulism outbreak among beef cattle in a semi-containment regime. The animals were fed corn silage and commercial feed and had access to a pasture of Guinea grass ( Panicum maximum ). Of the 150 steers in the herd, 22 (14.6% morbidity rate) presented clinical signs compatible with botulism and died (100% lethality rate). The 22 steers were clinically evaluated and eight were necropsied. The carcasses were evaluated macroscopically, and samples of the main organs were collected for laboratory testing. Ruminal and intestinal contents, and samples of the silage and animal feed provided were also collected. Botulinum toxin type C was identified in the ruminal contents of one steer and in the corn silage. Herein, the epidemiology, clinical signs, and laboratory findings regarding botulinum intoxication are emphasized for this outbreak. Our findings show the importance of keeping the silage well preserved because this represented a means of neurotoxin transmission that generated economic damage to the producer.